Efficacy of Vitamin D supplementation in gestational diabetes mellitus: Systematic review and meta-analysis of randomized trials - Rodrigues, Meline Rossetto Kron [UNESP]; Lima, Silvana Andréa Molina [UNESP]; da Silvia Mazeto, Glaucia Maria Ferreira [UNESP]; Calderon, Iracema Mattos Paranhos [UNESP]; Magalhães, Claudia Garcia [UNESP]; Ferraz, Guilherme Augusto Rago [UNESP]; Molina, Ana Claúdia; de Araújo Costa, Roberto Antônio [UNESP]; Nogueira, Vania dos Santos Nunes [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Public Library of Science (PLoS), 2019)
Background Trials have examined on the benefits of vitamin D supplementation in pregnant women. Objective This review aimed to evaluate whether oral vitamin D supplements, when given to pregnant women with gestational diabetes mellitus (GDM), would improve maternal and neonatal outcomes, compared with no treatment or placebo. Method We performed a systematic review following Cochrane methodology, and randomized trials were included where pregnant women with GDM received vitamin D supplementation versus placebo/no treatment or vitamin D and calcium versus placebo/no treatment. Primary outcomes were preeclampsia, preterm birth, cesarean delivery, gestational hypertension, and adverse events related to vitamin D supplementation. The search strategies were applied to the following databases: MEDLINE, Embase, LILACS, and CENTRAL. Similar outcomes in at least two trials were plotted using Review Manager 5.3 software. The quality of evidence was generated according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results The total of 1224 references were identified, eleven trials were potentially eligible, and six were included in this review (totaling 456 women). The meta-analysis of frequency of cesarean deliveries did not show significant differences between groups, none of the trials evaluated the remaining primary outcomes. For secondary outcomes, our results suggest that vitamin D supplementation in pregnant women with GDM may reduce newborn complications such as hyperbilirubinemia, polyhydramnios (RR: 0.40, 95% CI: 0.23 to 0.68; RR: 0.17, 95% CI: 0.03 to 0.89; respectively), and the need for maternal or infant hospitalization (RR: 0.13; 95% CI: 0.02 to 0.98; RR: 0.40, 95% CI: 0.23 to 0.69). However, the evidence was of low or very low quality. Conclusion We did not find moderate or high quality evidence indicating that vitamin D supplementation, when compared with placebo, improves glucose metabolism, adverse maternal and neonatal outcomes related to GDM in pregnant women.